Effects of mesenchymal stromal cells on monocyte differentiation to M1 phenotype and M1/M2 macrophage switching - E. Ya. Shevela; L. V. Sakhno; M. A. Tikhonova; E. V. Batorov; A. A. Ostanin; E. R. Chernykh (Бюллетень сибирской медицины)
Objective. Mesenchymal stromal cells (MSCs) promote the differentiation of unprimed macrophages (Mр) or classically activated M1 cells towards alternatively activated, M2 macrophages. The aim of the work was to study the ability of MSC to induce M1→M2 switching by comparing the MSC effects on polarized M1 macrophages and monocytes stimulated by granulocyte-macrophage colony-stimulating factor to M1 differentiation.Material and мethods. MSC were co-cultured with monocytes for 7 days or M1 macrophages for 48 hours in Transwell system to prevent direct cell-to-cell contacts. To characterize generated Mр, classical M2 marker CD206, allostimulatory activity in a mixed lymphocyte culture (MLC), and the ability to secrete pro-/antiinflammatory mediators were analyzed.Results. Co-cultivation of MSCs and M1 macrophages led to the appearance of phenotypic (increased expression of CD206) and functional (decrease in allostimulatory activity) features of M2 phenotype. When MSCs were cultured with monocytes in the M1-inducing medium, generated Mр elicited a pronounced stimulating activity in MLC similar to that of M1 (stimulation index 3.45 and 3.4, p = 0.46) and significantly higher than allostimulatory activity of M2 cells (3.45 vs 2.2, p = 0.03). In addition, MSCs did not influence the expression of CD206, as well as the production of pro- (IL-1β, TNF-α, IL-6, IL-12) and anti-inflammatory (IL1-ra, IL-4, IL-10) cytokines, immunoregulatory cytokines (IFN-γ, IL-17) and chemokines (IP-10, MCP-1, MIP-1b, Rantes, Eotaxin).Conclusions: The ability of MSC to induce the M2 phenotype depends on the stage of differentiation of monocyte/macrophages. MSCs promote M1→M2 switching in cultures of polarized M1 macrophages. In contrast, when MSCs interacted with monocytes in M1-inducing medium, a population of M1-like macrophages is formed with high allostimulatory activity and typical for M1 spectrum of produced cytokines and chemokines.